Evaluation of the pharmacokinetics, pharmacodynamics, and liver ultrasound imaging characteristics of a novel perfluoropropane microbubble in Chinese volunteers - Li, Pengfei; Du, Ping; Zhao, Zhixia; Jia, Fei; Yu, Weiyue; Qu, Peng; Li, Jiangfan; Wang, Xuhong; Liu, Lihong (Frontiers in Pharmacology, 2025)
Background and ObjectivePerfluoropropane (PFP), a lipidbased microbubble preparation, is a novel ultrasound contrast agent. This study aims to evaluate the pharmacokinetics, pharmacodynamics, and liver ultrasound enhancement characteristics of PFP microbubble, a novel ultrasound contrast agent, in healthy Chinese subjects.MethodsThis study is a multicenter, open-label, three-doses, single-dose Phase I clinical trial of the PFP ultrasound contrast agent conducted in healthy male and female volunteers. Screening healthy subjects for inclusion in the trial, with a pre-trial and three dose groups of low (6 μL/kg), medium (12 μL/kg), and high (18 μL/kg), were conducted sequentially from the low-dose group to the high-dose group.ResultsIn this study, a total of 146 volunteers were screened, and 39 subjects were enrolled, including 3 participants in the pilot study and 12 participants in each of the low, medium, and high dose groups. No subjects withdrew early from the trial, and all 39 individuals completed the entire trial. After injection, PFP is primarily distributed in the blood and rapidly peaks and disappears in both blood and exhaled gas. Pulmonary excretion is the primary excretion pathway for PFP. The cumulative excretion rates of peak concentration (Cmax), area under the curve (AUC0-t and AUC 0−∞), and exhaled gas in blood and exhaled gas do not follow a dose linear relationship due to individual differences; however, the observed average values demonstrate an increasing trend. Significant contrast enhancement was observed after injection of various doses of PFP. With low doses (6 μL/kg), the agent meets the requirements for liver ultrasound diagnosis in this study. Overall, PFP has good safety among healthy Chinese subjects.ConclusionThis study systematically evaluated the pharmacokinetics and pharmacodynamics of PFP in blood and exhaled breath, as well as the ultrasound characteristics of the liver. We observed for the first time the dynamic changes in blood and exhaled breath between different doses of PFP, and also determined for the first time the appropriate ultrasound diagnostic dose for the experimental formulation. This study presents a valuable methodological framework and reference point for future research in this field.Clinical Trial RegistrationThis study was registered on 24 November 2020 at the Chinese Clinical Trial Registry (CTR20202343).